WHICH HOTEL ATTRIBUTES MATTER FOR MASS TOURIST: A QUALITATIVE RESEARCH ON TOURISTS’ REVIEW ON TRIP ADVISOR - Çizel, Beykan; Çizel, Rabia; Ajanovic, Edina (PEOPLE: International Journal of Social Sciences, 2015)
Development of Internet and especially Web2.0 technologies introduced numerous opportunities for tourism industry. Due to new web-based platforms where customers can buy, evaluate and comment the products and/or services, Internet has become an important source of data that can be used in academic research. Therefore, the researchers of this paper aimed to determine the most important attributes that affect hotel choice based on the comments on one of the world’s most popular online travel platforms-Trip Advisor. In the scope of the research are reviews and comments on hotels found in touristic center of Belek in one of the most popular mass tourism destinations – Antalya. As a result of the content analysis, there are three groups of attributes which matter for mass tourists in terms of their hotel choice: attributes regarding destination, service and hotel, with attributes under the service category representing the most dominant ones in terms of hotel choice. The results of this research may be useful to hotel investors and potential hotel guests as well contribute to the overall knowledge about online travel behavior and preferences.